2022
DOI: 10.1038/s41598-022-20830-3
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ROS mediated genomic instability, apoptosis and G0/G1 cell cycle arrest by erbium oxide nanoparticles in human hepatic Hep-G2 cancer cells

Abstract: The remarkable physical and chemical characteristics of noble metal nanoparticles, such as high surface-to-volume ratio, broad optical properties, ease of assembly, surfactant and functional chemistry, have increased scientific interest in using erbium oxide nanoparticles (Er2O3-NPs) and other noble metal nanostructures in cancer treatment. However, the therapeutic effect of Er2O3-NPs on hepatic cancer cells has not been studied. Therefore, the current study was conducted to estimate the therapeutic potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The induction of oxidative stress-mediated apoptosis in tumor cells, including HepG2 cells, was already reported in several earlier studies [51,52]. A recent report from Safwat et al [53] has shown that green-synthesized NPs encourage ROS-mediated apoptosis G0/G1 cell cycle arrest in HepG2 cells, which supports the findings of the current work.…”
Section: Analysis Of Endogenous Ros Accumulationsupporting
confidence: 91%
“…The induction of oxidative stress-mediated apoptosis in tumor cells, including HepG2 cells, was already reported in several earlier studies [51,52]. A recent report from Safwat et al [53] has shown that green-synthesized NPs encourage ROS-mediated apoptosis G0/G1 cell cycle arrest in HepG2 cells, which supports the findings of the current work.…”
Section: Analysis Of Endogenous Ros Accumulationsupporting
confidence: 91%
“…This is in agreement with the observed correlations between MT gene expression and LPO ( r = 0.59) in the present study. This was also found with Er oxide nanoparticles, i.e., induced oxidative stress leading to cell cycle arrests and apoptosis (Safwat et al 2022 ).…”
Section: Discussionmentioning
confidence: 64%